2006
DOI: 10.1021/ja057692h
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Protein Kinase-Inducible Domain

Abstract: Protein phosphorylation is a critical regulatory strategy. New tools are necessary which may be used to interrogate and are responsive to the activities of protein kinases and phosphatases. We have used protein design to develop a protein motif, termed a protein kinase-inducible domain, whose structure is dependent on its phosphorylation state. Based on an EF hand calcium-binding loop, the key design element is the replacement of a structurally critical Glu residue, which binds metal in a bidentate manner, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 20 publications
1
51
0
Order By: Relevance
“…Our lab has shown that the phosphorylation state of a peptide can dramatically increase its affinity for metal ions 221,222. As a consequence, Tb 3+ can be an effective reporter of phosphorylation status 221,223. In these cases, the peptides are short sequences resembling calcium-binding loops where the phosphorylated amino acid is either embedded within the peptide, as in DPDNEA(pY)EMPSEEG,221 or as the anchoring metal-ligating residue near the end of the peptide, as in DKNADGWIDRA(pS)LA,223 where pY and pS are phosphotyrosine and phosphoserine, respectively.…”
Section: Metal Complexes That Bind/release Small Moleculesmentioning
confidence: 99%
“…Our lab has shown that the phosphorylation state of a peptide can dramatically increase its affinity for metal ions 221,222. As a consequence, Tb 3+ can be an effective reporter of phosphorylation status 221,223. In these cases, the peptides are short sequences resembling calcium-binding loops where the phosphorylated amino acid is either embedded within the peptide, as in DPDNEA(pY)EMPSEEG,221 or as the anchoring metal-ligating residue near the end of the peptide, as in DKNADGWIDRA(pS)LA,223 where pY and pS are phosphotyrosine and phosphoserine, respectively.…”
Section: Metal Complexes That Bind/release Small Moleculesmentioning
confidence: 99%
“…[3][4][5][6] The incorporation of lanthanides within designed proteins provides a functional handle to potentially introduce long-lifetime fluorescence, luminescence resonance energy transfer over large distances, orientation in magnetic fields, and hydrolytic activity into proteins. [7][8][9][10][11] Although lanthanides are not known to exist natively within proteins, lanthanides have long been used as spectroscopic probes of structure and function in calcium-binding proteins; lanthanides bind to calcium-binding sites in proteins due to similarities in metallic ionic radii and hardness. [7,8,12,13] EF-hand proteins represent the smallest and most broadly utilized natural calcium-binding proteins, comprising a 70 amino-acid motif that binds two calcium ions.…”
Section: Introductionmentioning
confidence: 99%
“…Phopshorylated residues can also induce structural changes via metal binding 1518. However, to our knowledge, no one has investigated whether phosphorylation can result in a repulsive interaction with a hydrophobic or aromatic group that could affect peptide structure.…”
Section: Introductionmentioning
confidence: 99%